Integration of Perinatal Mental Health into Maternal and Child Care: Progress and Challenges from the World Health Organization's Perspective - Paricio-del-Castillo, Rocío (European Journal of Mental Health, 2024)
Introduction: Perinatal mental health is essential for maternal and child well-being, and its promotion has the potential to improve health outcomes while reducing social and healthcare costs in both the short and long term. The World Health Organization (WHO) is making efforts to integrate mental health into maternal and child health services on a global scale.Areas covered: Since 2001, the WHO has addressed mental health in its documentation, emphasizing the importance of safeguarding child health and supporting caregivers. However, perinatal mental health has primarily been developed within maternal and child health care strategies. The publication of the “Guide for Integration of Perinatal Mental Health in Maternal and Child Health Services” (2022) marks a significant advancement through providing specific recommendations for implementing perinatal mental health within healthcare systems.Expert opinion: Despite these advances, integrating perinatal mental health into healthcare systems faces challenges, including the integration of care for fathers and families, training healthcare professionals, and considering women’s lived experiences. Barriers include gender and age discrimination, mental health stigma, and deficiencies in healthcare infrastructure, particularly in low- and middle-income countries (LMICs).Conclusion: Comprehensive maternal and child health care has the potential to improve maternal and child well-being while reducing long-term costs. To enhance perinatal mental health globally, it is essential to integrate it at all levels of healthcare, incorporating user experiences, strengthening professional training, and ensuring adequate resources within healthcare systems.